MODERN METHODS OF TEACHING VOCABULARY IN HIGH SCHOOL - Madaminova Umida Rustam qizi (Galaxy International Interdisciplinary Research Journal, 2022)
It is important to claim that, since English has become a universal and dominant source to communicate in the world, the interest of learning this language is increasing dramatically. But people can't use any languages without vocabulary and this paper analyses the vocabulary of a language and vocabulary teaching methods and techniques and studies some methods.